The Effect of Employee Absenteeism and Turnover on Innovation and Organizational Performance - Devy Senza Maulina; Wawan Prahiawan; Liza Mumtazah (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2024)
This research was conducted to determine the influence of employee absenteeism and turnover on innovation and organizational performance. The variables used in this research are employee absenteeism and turnover, where how much influence these two variables have on the success of innovation and organizational performance. The data collection method uses literature study which is then searched for research gaps from several articles/journals in this research. The research results show that employee absenteeism and turnover have a negative and significant effect on innovation and organizational performance. The higher the level of employee absenteeism, the more difficult it will be for the employee to contribute to organizational performance. This means that the higher the level of absenteeism, the lower the innovation and organizational performance. High employee turnover can also affect organizational performance and innovation. Frequent loss of competent employees can hamper innovation and organizational performance. This means that the higher the employee turnover rate, the lower the innovation and organizational performance. To improve organizational performance, innovation is very important. If a company has an environment that supports innovation, its employees can become more innovative and creative. This means that innovation has a significant positive effect on organizational performance.